Pulmonary involvement in Anti‐Neutrophil Cytoplasmic Antibody Associated Vasculitis: A single centre case series. Issue 11 (21st October 2022) - Bell, Peter T.; Sheehy, Robert; Droney, Luke; Prain, Kerri; Wong, Richard; Keir, Gregory J.
Abstract: Anti‐Neutrophil Cytoplasmic Antibody associated Vasculitides (AAV) comprise a rare group of disorders in which respiratory tract involvement is variable and often severe. The rarity and heterogeneity of AAV makes this a challenging condition to diagnose and manage. In this single‐centre case series of 44 patients with AAV‐associated respiratory disease, we provide an overview of disease manifestations, management aspects and treatment outcomes. Data from this case series highlight the real‐world diagnostic and therapeutic challenges of the AAV respiratory disease spectrum; including uncertainties in the management of fibrosing interstitial lung disease, tracheobronchial stenosis and diffuse alveolar haemorrhage. Abstract : Here, we describe the spectrum of disease manifestations and treatment outcomes in a large single‐centre case series of patients with Anti‐Neutrophil Cytoplasmic Antibody vasculitis ‐associated respiratory disease. This series highlights the diagnostic and treatment challenges encountered by physicians involved in the care of these patients, including the management of diffuse alveolar haemorrhage, relapsing tracheobronchial disease, and fibrosing interstitial lung disease.